2023
DOI: 10.1002/uog.26136
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of prenatal valacyclovir for congenital cytomegalovirus infection: systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis shows that valacyclovir administered to pregnant women with cytomegalovirus (CMV) infection reduces the risk of congenital CMV infection and increases the likelihood of infection being asymptomatic. However, no evidence of significant improvement of other CMV-related adverse perinatal outcomes was found. What are the clinical implications of this work?Prenatal valacyclovir administration should be considered when first-trimester maternal CMV infection is suspected on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(91 reference statements)
0
28
0
2
Order By: Relevance
“…The first studies, which did not include recent data on the efficacy of valaciclovir in preventing maternal-fetal transmission, showed that routine CMV serology screening could be costeffective if antenatal treatment was significantly effective in reducing the risk of neonatal disease [137,138]. Since then, a meta-analysis of the results of three recent studies has concluded that valaciclovir is effective for secondary prevention of maternal-fetal transmission of CMV [115,[139][140][141]]. An American cost-effectiveness analysis, based on a cost of USD 100,000 per quality-adjusted life year (QALY), demonstrated that universal first-trimester serological screening for primary maternal CMV infection is not cost-effective as it resulted in only 14 fewer children being affected with cytomegalovirus per 100,000 pregnancies when compared to usual care [142].…”
Section: Diagnosis Of Maternal Infection and Screening Strategiesmentioning
confidence: 99%
“…The first studies, which did not include recent data on the efficacy of valaciclovir in preventing maternal-fetal transmission, showed that routine CMV serology screening could be costeffective if antenatal treatment was significantly effective in reducing the risk of neonatal disease [137,138]. Since then, a meta-analysis of the results of three recent studies has concluded that valaciclovir is effective for secondary prevention of maternal-fetal transmission of CMV [115,[139][140][141]]. An American cost-effectiveness analysis, based on a cost of USD 100,000 per quality-adjusted life year (QALY), demonstrated that universal first-trimester serological screening for primary maternal CMV infection is not cost-effective as it resulted in only 14 fewer children being affected with cytomegalovirus per 100,000 pregnancies when compared to usual care [142].…”
Section: Diagnosis Of Maternal Infection and Screening Strategiesmentioning
confidence: 99%
“…Both guidelines concluded that there is insufficient evidence to support antiviral therapy. A recent systematic review and meta‐analysis on prenatal valaciclovir for congenital CMV infection concluded that valaciclovir significantly lowered the risk of transmission when maternal infection was acquired in the first trimester of pregnancy 24 . Severe foetal sequelae are only common following maternal infection in the periconception period or in the first trimester 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The emerging evidence for the use of valaciclovir for the prevention of foetal infection after maternal primary infection in the first trimester makes this review timely and topical. 24 Screening is predicated upon an established course of action following a positive screening test result, 25 such as interventions that would prevent or reduce the transmission from mother to foetus or treatment of foetal infection. The 2020 randomised controlled trial by Shahar-Nissan et al showed a significant reduction in foetal infection from 30% to 11%.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital CMV is the most common infectious cause of sensorineural hearing loss, neurodisability and cerebral palsy. There is emerging data on the use of valaciclovir to prevent in utero transmission of CMV following maternal primary infection, 18 which could be a rationale for implementing routine serological screening in pregnancy. However, a systematic review of consensus statements and guidelines found that no health authority currently recommends universal prenatal serological screening for maternal CMV infection 19 .…”
Section: Figurementioning
confidence: 99%